HUMAN RESOURCES THAT MUST BE PREPARED IN EDUCATIONAL ENTREPRENEURSHIP - Rindanigsih, Ida; Irsandi, Faisal (Antis Publisher, 2023)
The scarcity of labor among entrepreneurs is influenced by various factors, ranging from financial management, marketing, to the difficulty of finding raw materials for a company's products. The Industrial Revolution 4.0 also brings unique challenges to society, especially entrepreneurs in the field of education. Ease of access to information and knowledge indirectly impacts some businesses that are run offline and manually. The biggest challenge of entrepreneurship in the Society 5.0 era is to improve the ability and skills to adapt to various rapid changes in the business environment and society. This research aims to develop human resource management in educational institutions and human resource entrepreneurship in Islamic educational institutions. From the results of this study, human resource management in education includes all policies, activities, and considerations aimed at utilizing human resources (in this case educators and training staff) to achieve goals. understand that this includes efforts. The goals and strategies of human resource development education in Islamic educational institutions are best achieved by developing a vision/mission, promoting innovation, and building an entrepreneurial culture.